Interleukin‐3‐mediated regulation of β‐catenin in myeloid transformation and acute myeloid leukemia. Issue 1 (5th March 2014) - Sadras, Teresa; Perugini, Michelle; Kok, Chung H.; Iarossi, Diana G.; Heatley, Susan L.; Brumatti, Gabriela; Samuel, Michael S.; To, Luen B.; Lewis, Ian D.; Lopez, Angel F.; Ekert, Paul G.; Ramshaw, Hayley S.; et al.
Abstract : IL‐3 activates β‐catenin in Hox‐transformed myeloid cells, and primary AML samples, presenting a novel axis for targeted inhibition of β‐catenin in some patients with AML. Abstract : Aberrant activation of β‐catenin is a common event in AML and is an independent predictor of poor prognosis. Although increased β‐catenin signaling in AML has been associated with oncogenic translocation products and activating mutations in the FLT3R, the mechanisms that activate β‐catenin in AML more broadly are still unclear. Here, we describe a novel link between IL‐3 signaling and the regulation of β‐catenin in myeloid transformation and AML. In a murine model of HoxB8 and IL‐3 cooperation, we show that β‐catenin protein levels are modulated by IL‐3 and that Cre‐induced deletion of β‐catenin abolishes IL‐3‐dependent growth and colony formation. In IL‐3‐dependent leukemic TF‐1.8 cells, we observed increased β‐catenin protein levels and nuclear localization in response to IL‐3, and this correlated with transcriptional induction of β‐catenin target genes. Furthermore, IL‐3 promoted β‐catenin accumulation in a subset of AML patient samples, and gene‐expression profiling of these cells revealed induction of WNT/β‐catenin and TCF4 gene signatures in an IL‐3‐dependent manner. This study is the first to link β‐catenin activation to IL‐3 and suggests that targeting IL‐3 signaling may be an effective approach for the inhibition of β‐catenin activity in some patients with AML.